MECHANISMS OF EDUCATIONAL STUDY OF STUDENTS ON THE BASIS OF MODERN PEDAGOGICAL TECHNOLOGIES - Tangirov Eldor Sayfullayevich (Journals Park Publishing, 2022)
The relevance of the article is determined by the need for ethno-cultural socialization of teachers to work in a multicultural educational space. The peculiarities of the process of ethno-cultural socialization of future teachers require the creation of a model. The purpose of the article is to model the process of ethno-cultural socialization of future teachers. The research methodology is based on the principles of consistency, axiology, humanization, personal orientation, the connection of learning with life, the dialogue of cultures. The authors formulated the principles and methods according to which the pedagogical work on the ethno-cultural socialization of future teachers was built. The model of ethno-cultural socialization of future teachers is developed, in which the process of ethno-cultural socialization is revealed on the basis of the proposed criteria, indicators and levels. Pedagogical conditions and functions of ethno-cultural education are proposed.
Keywords: modeling; ethno; cultural socialization